The archaeology of medieval ecclesiastical settlement in the barony of Lower Dundalk, Co. Louth - Ryan, Vanessa (Trinity College (Dublin, Ireland). Department of History, 2010)
This thesis is a regional study of the archaeology of medieval ecclesiastical settlement in the barony of Lower Dundalk, Co. Louth, from c. 1000-1650. In the absence of excavation, the primary aim of this thesis was to devise a methodology for the consistent study of the archaeology of the sixteen medieval ecclesiastical sites which are known to have existed in this barony throughout the study period, and, to facilitate this end, the thesis is divided into six chapters. Chapter I outlines the aim, scope and remit of the thesis and also provides a general historical background to the study area. Chapter II details a statement of the methodology as well as some alternative avenues of research. Chapter III discusses the archaeology of the pre-Norman foundations in the barony from c. 1000-1189 which were located at Faughart, Proleek, Roosky and Comamucklagh; it also examines the re-use and development of the sites at Faughart, Proleek and Roosky from c. 1189-1650. Chapter IV assesses the archaeology of the eight rural Anglo-Norman churches which were located at Ballymascanlan, Mountbagnall, Castletowncooley, Templetown, Willville, Grange, Muchgrange and Knocknagoran, while Chapter V analyses the archaeology of the four urban ecclesiastical sites which were situated in the medieval town of Carlingford; the Church of the Holy Trinity, St. Mary’s Church, St. Michael’s Church and the Dominican Abbey.
Keywords: Medieval History, Ph.D.; Ph.D. Trinity College Dublin